Upcoming epidemic of asbestos-related malignant pleural mesothelioma in Taiwan: A prediction of incidence in the next 30 years - Ro-Ting Lin; Yu-Yin Chang; Jung-Der Wang; Lukas Jyuhn-Hsiarn Lee (Journal of the Formosan Medical Association, 2019)
Background/Purpose: Globally, asbestos-related diseases (ARDs) keep rising over the coming decades. The epidemic of ARDs will be a burden on public health. We aimed to predict the malignant pleural mesothelioma (MPM) incidence in the next 30 years for Taiwan based on historical asbestos consumption. Methods: We collected annual data on local asbestos consumption during 1939–2015 and sex-specific incidence of pleural cancer as a proxy for MPM during 1979–2013. We applied Poisson log-linear models to predict future MPM numbers under the assumption that latency periods between asbestos exposure and MPM incidence were between 25 and 45 years. Results: Asbestos consumption reached a peak in the 1980s, with a total of 668 thousand metric tons during 1939–2015. The observed number of MPM incidence increased by 9- and 6-fold in males and females during 1979–2013, with a cumulative number of 907. Given a latency period of 31 years, MPM incidences were expected to peak around 2012–2016 for males and 2016–2020 for females. In 2017–2046, the predicted total number of new MPM might reach 659 cases (95% confidence interval = 579–749); and the male to female ratios ranged from 1.8 to 2.8. Conclusion: The MPM epidemic in Taiwan will likely peak in 2012–2020 as a result of local asbestos consumption. Approximately 659 new MPM cases in the next 30 years warrant an urgent need to implement a total asbestos ban and put more resources on a comprehensive surveillance, diagnosis, and follow-up health care system for ARDs. Keywords: Asbestos, Mesothelioma, Pleural cancer